On an EUV Atmospheric Simulation Chamber to Study the Photochemical Processes of Titan’s Atmosphere - Bourgalais, Jérémy (Sci Rep, 2020)
The in situ exploration of Titan’s atmosphere requires the development of laboratory experiments to understand the molecular growth pathways initiated by photochemistry in the upper layers of the atmosphere. Key species and dominant reaction pathways are used to feed chemical network models that reproduce the chemical and physical processes of this complex environment. Energetic UV photons initiate highly efficient chemistry by forming reactive species in the ionospheres of the satellite. We present here a laboratory experiment based on a new closed and removable photoreactor coupled here to an Extreme Ultraviolet (EUV) irradiation beam produced by the high-order harmonic generation of a femtosecond laser. This type of EUV stable source allow long-term irradiation experiments in which a plethora of individual reactions can take place. In order to demonstrate the validity of our approach, we irradiated for 7 hours at 89.2 nm, a gas mixture based on N(2)/CH(4) (5%). Using only one wavelength, products of the reaction reveal an efficient photochemistry with the formation of large hydrocarbons but especially organic compounds rich in nitrogen similar to Titan. Among these nitrogen compounds, new species had never before been identified in the mass spectra obtained in situ in Titan’s atmosphere. Their production in this experiment, on the opposite, corroborates previous experimental measurements in the literature on the chemical composition of aerosol analogues produced in the laboratory. Diazo-compounds such as dimethyldiazene (C(2)H(6)N(2)), have been observed and are consistent with the large nitrogen incorporation observed by the aerosols collector pyrolysis instrument of the Huygens probe. This work represents an important step forward in the use of a closed cell chamber irradiated by the innovative EUV source for the generation of photochemical analogues of Titan aerosols. This approach allows to better constrain and understand the growth pathways of nitrogen incorporation into organic aerosols in Titan’s atmosphere.